Strategies for Improving Education Quality via New Student Admission Management - Elly, Elly; Ismail, Ismail; Sofyan, Hizir (Heca Sentra Analitika, 2024)
The study investigates the management of the zoning system for new student admissions (PPDB) at SD Negeri 3 Jeumpa and SD Negeri 4 Kuala Batee in Aceh Barat Daya Regency, Indonesia. Using a qualitative phenomenological approach, it explores the planning, implementation, supervision, and evaluation processes. Key findings reveal that while adherence to Ministry of Education guidelines ensured systematic planning and implementation, challenges such as online registration difficulties, quota constraints, and misinformation persist. Supporting factors include skilled personnel, infrastructure, and collaboration, whereas hindrances involve resource limitations and community misinformation. The study recommends sustained evaluation and strategic improvements to enhance the PPDB process and advance educational quality in the region.